Preeclampsia and Pregnancy-Related Hypertensive Disorders - Karumanchi, S. Ananth (Hypertension, 2015)
Our understanding of hypertension during pregnancy and in particular, preeclampsia has changed dramatically over the last decade. During the last year (2014–15), several articles published in Hypertension have provided important insights into the pathogenesis of preeclampsia and its related complications(1–38). In addition, Hypertension also published some key research communications that translated important basic science observations into the clinic. Some of these articles are briefly discussed, highlighting their significance to our understanding of the mechanism of the disease, to predict the disease and treat or prevent hypertension during pregnancy and other preeclampsia related complications.